'You need to know in order to help': how HIV-related stigma obstructs pastoral care in Kenyan primary schools. Issue 2 (2nd April 2020) - Brainin, Frederik; Merrild, Klara; Rueskov, Vivian; Skovdal, Morten
ABSTRACT: In low-resource and high HIV prevalence settings, schools are increasingly called upon as sites of care and support for vulnerable children. It is therefore crucial to understand the processes through which teachers take on pastoral care roles in response to the needs of vulnerable learners. As pastoral care is often contingent on teacher's being aware of learner's vulnerabilities and needs, we examine information-sharing between learners, their parents, and teachers. We draw on eight individual interviews conducted with teachers from three rural primary schools located in high HIV prevalence settings of the Siaya district of Western Kenya. The interviews were recorded, transcribed, and analysed using thematic network analysis. Our analysis revealed that HIV-related stigma made it difficult for vulnerable learners to disclose their vulnerabilities to teachers, fearing the repercussions of what might happen if other members of the school community would become aware of their association with HIV. When teachers sought out parents for more information, they were often met with denial of their vulnerabilities. This paper provides valuable insights into some of the difficulties primary school teachers face in ascertaining the pastoral care needs of vulnerable learners. It highlights that HIV-related stigma is a critical barrier for teachers to adopt a pastoral care role in high HIV prevalence communities of western Kenya.